2018
DOI: 10.1371/journal.pone.0206639
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence, frequency of leptospiuria, and associated risk factors in horses in Kansas, Missouri, and Nebraska from 2016-2017

Abstract: Leptospirosis is a worldwide veterinary and public health concern, and well recognized infectious disease of horses. Seroprevalence rates vary with geography, but many studies have confirmed a high exposure rate. The correlation between seropositivity and shedding status has not been made in horses, however. The aims of this study were to use semi-nested PCR on urine from apparently healthy horses to determine period prevalence of leptospiral shedding and to correlate these findings with MAT results to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
4
12
0
Order By: Relevance
“…As found in the current study, similar studies in Kansas [ 32 ] and Switzerland [ 33 ] reported high titres in the horses sampled that could be consistent with active infection, but no clinical signs of disease were reported in the horses. High antibody levels do not indicate if a horse is currently shedding Leptospira , as horses can be both seropositive or negative and be shedding the bacteria [ 8 , 32 ]. Although no inference about active infections in the cohort of horses reported in this study can be made, horses with active infections that are shedding may be a risk to both animals and people in contact with them [ 35 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As found in the current study, similar studies in Kansas [ 32 ] and Switzerland [ 33 ] reported high titres in the horses sampled that could be consistent with active infection, but no clinical signs of disease were reported in the horses. High antibody levels do not indicate if a horse is currently shedding Leptospira , as horses can be both seropositive or negative and be shedding the bacteria [ 8 , 32 ]. Although no inference about active infections in the cohort of horses reported in this study can be made, horses with active infections that are shedding may be a risk to both animals and people in contact with them [ 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…A quarter of the horses in the cohort tested positive to at least one serovar, which is the same as the seroprevalence rates reported in Korea (25%) [ 28 ] and slightly lower than a study in Australia (29%) [ 29 ]. Studies in Brazil, Italy, and North America have reported higher rates of 45%, 67%, and 77% of horses testing positive to at least one serovar, respectively [ 30 , 31 , 32 ]. Direct comparisons of seroprevalence across geographic regions may be difficult due to variations in the positive titre cut-off used between studies and differences in endemic serovars across regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seroprevalences of 58.5% and 79% were found in Switzerland and in the Netherlands, respectively [14,15]. In a Brazilian study, the percentage of seropositivity was 71.4% [16] and a recent study carried out in some States of the American Midwest reported a 77% seroprevalence in healthy horses [17]. Surprisingly, a group of Italian researchers [10,11] reported a seroprevalence of 11.4% and 1.5%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Serovar Bratislava is considered to be a host-adapted serovar for horses, which is reflected by high seroprevalence in the absence of clinical signs. 4,15,18,20 Serovars for which the horse is the incidental host generally cause more significant clinical disease. In horses, the serovars most commonly associated with severe morbidity are Pomona, notably Pomona strain Kennewicki, 7 and Grippotyphosa.…”
mentioning
confidence: 99%